Thermozyme Amylase from Enterobacter sp Extremophiles in Bioethanol Production - Gustina Indriati; Ruth Rize Paas Megahati (Journal of Science and Science Education, 2021)
Bioethanol is an alternative fuel to replace fossil fuels due to the reduction of fossil fuels. Bioethanol is produced from starch and converted to sugar by thermozyme amylase. Thermozyme amylase produced by thermophile bacteria can be obtained from Pariangan hot springs which have a temperature of  55 °C, pH of 9.2, and have a high level of bacterial diversity. The aim of this study was to obtained isolates of thermozyme amylase-producing bacteria that have the potential for bioethanol production. The research method were bacteria isolation, amylase stability test, temperature and pH optimization, and bioethanol production. The result showed that Enterobacter sp has been isolated from Pariangan hot springs is stable up to 5 hours of incubation, temperature and pH optimum was 85 °C, pH 8.5, and fructose as a carbon source. Thermozyme amylase converts starch into sugar under optimum conditions with a yield of 9.8% bioethanol